2009
DOI: 10.4049/jimmunol.0900263
|View full text |Cite
|
Sign up to set email alerts
|

Selective Up-Regulation of Intact, but Not Defective env RNAs of Endogenous Modified Polytropic Retrovirus by the Sgp3 Locus of Lupus-Prone Mice

Abstract: Endogenous retroviruses are implicated in the pathogenesis of systemic lupus erythematosus (SLE). Because four different classes of endogenous retroviruses, i.e., ecotropic, xenotropic, polytropic, or modified polytropic (mPT), are expressed in mice, we investigated the possibility that a particular class of endogenous retroviruses is associated with the development of murine SLE. We observed >15-fold increased expression of mPT env (envelope) RNA in livers of all four lupus-prone mice, as compared with those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(82 citation statements)
references
References 58 publications
5
76
0
Order By: Relevance
“…However, an endogenous retrovirus is not a likely source of dsRNA in B6.NZBc13 mice, as almost all endogenous retroviruses are not replication competent due to post-integration mutations and deletions, suggesting a lack of active viral infection. Moreover, the Sgp3 locus was found to control the gp70 expression of a modified polytropic (mPT) provirus (ssRNA virus), and not of the xenotropic proviruses (NZB-X1 or NZB-X2) shown to accelerate anti-chromatin antibody production in NZB mice [28][29][30]. Interestingly, it has been previously reported that in vivo exposure to poly(I:C) potently increases serum gp70 levels in NZB mice, which suggested a potential role for gp70 as an acute phase reactant [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, an endogenous retrovirus is not a likely source of dsRNA in B6.NZBc13 mice, as almost all endogenous retroviruses are not replication competent due to post-integration mutations and deletions, suggesting a lack of active viral infection. Moreover, the Sgp3 locus was found to control the gp70 expression of a modified polytropic (mPT) provirus (ssRNA virus), and not of the xenotropic proviruses (NZB-X1 or NZB-X2) shown to accelerate anti-chromatin antibody production in NZB mice [28][29][30]. Interestingly, it has been previously reported that in vivo exposure to poly(I:C) potently increases serum gp70 levels in NZB mice, which suggested a potential role for gp70 as an acute phase reactant [31].…”
Section: Discussionmentioning
confidence: 99%
“…All RNA samples were treated with rDNase 1 (Ambion) before reverse transcription. RNA (100 ng) from each sample was reverse transcribed with oligo(dT) [12][13][14][15][16][17][18] using the SuperScript FirstStrand Synthesis System (Invitrogen). PCR primers were as follows: gp70 forward 5Ј CCGCGTCCCCATTGGGCCTAATCC 3Ј; gp70 reverse 5Ј GGACGGCAACCCCTTCG-TAGTAGG 3Ј.…”
Section: Methodsmentioning
confidence: 99%
“…While the exact identity of these loci is unknown, there is a strong link to endogenous retroviral expression in B/W mice: Mouse serum gp70 (produced by the liver) is very similar to MLV gp70 and is present in virtually every mouse strain, but only lupus-prone strains produce auto-antibodies to (retroviral) gp70 (14). In the production of anti-gp70 auto-antibodies, the Toll-like receptor 7 (TLR7) plays a critical role (15). Furthermore, mice deficient in TLR7, but not mice deficient in TLR9, have ameliorated lupus disease (16).…”
mentioning
confidence: 99%
“…First, the MuERV envelope glycoprotein, gp70, is considered to be an antigen against which a TLR7-dependent autoimmune response is directed in lupus-prone mice (Yoshinobu et al, 2009). The expression of gp70 is increased following activation of TLR7 and -9 in a mouse model of lupus (Baudino et al, 2010), providing a direct link between TLR activation and the upregulation of MuERV expression.…”
Section: Tlrs and Hervsmentioning
confidence: 99%
“…TLR7 was found to be involved in the germinal centre reaction, which facilitates antibody production and class switching, specifically in the acute response to murine exogenous retroviruses (Browne, 2011(Browne, , 2013. Furthermore, TLR7 was critical for the production of autoantibodies to gp70 (Yoshinobu et al, 2009), and mice lacking TLR7 were unable to produce antibodies to MuERVs (Yu et al, 2012). It was proposed that MuERVs are activated sporadically and that this allows for a protective, TLR7-dependent antibody response to control MuERV viraemia (Yu et al, 2012).…”
Section: Tlrs and Hervsmentioning
confidence: 99%